Plasticidade de espécies de fitofisionomias do cerrado à disponibilidade de luz e água - Ribeiro, Paula Rodrigues Gayer (2015)
The Cerrado is a vegitational domain comprised by phytophysiognomies that range from forests to fields. Despite being submitted to similar climatic conditions, the topographic conditions cause distinct water and radiation availability. Therefore, forest phytophysiognomies tend to occur with higher water availability. The opposite pattern can be observed in savanna phytophysiognomies. Pimenta pseudocaryophyllus (Gomes) Landrum and Machaerium opacum Vogel occur in forest phytophysiognomies, while Tabebuia serratifolia (Vahl) Nich and Zeyheria montana Mart are found in savanna phytophysiognomies. This might lead to distinct response patterns. In this work, we aimed at verifying the contrasting physiological behavior in relation to the different water and radiation availabilities of the species, using a completely randomized design in a 2x3x2 factorial scheme. During the experimental period, we performed evaluations regarding gas exchange, fluorescence and biochemical analyses. All data were submitted to Principal Component Analysis (PCA). We verified that T. serratifolia is capable of adjusting its physiological responses, enabling the control of gas exchanges according to water availability and environment lighting. In general, Z. montana, under full sunlight, regardless of water availability, presents higher photosynthesis and stomatal conductance. For plants in insulfilm, there was difference in behavior according to water availability. P. pseudocaryophyllus plants, in PS and S environments, presents very similar behavior, with strong dependence of gas exchange variables, and low dependence of the antioxidant system. M. opacum plants presented the same behavior in all studied conditions, presenting higher dependency of gas exchanges and antioxidant systems. We can conclude that T. serratifolia presents low plasticity, and Z. montana shows high plasticity. P. pseudocaryophyllus presents typical behavior in forest environment, and M. opacum is one of the most capable of overcoming global climatic changes.